Performance of refrigeration unit using monitoring of temperature, humidity and power consumption of freezer machine at Jaya Bahari cold storage - Nugrowibowo, Radityo; Sawiji, Asri; Fahmi, Muhammad Yunan (UIN Sunan Ampel Surabaya, 2023)
Fishery products generally spoil more quickly than other animal meat products. After being caught, fish will experience changes in quality, the level of these changes will determine the shelf life of the fish. Handling fresh fish is the most important aspect of a fisheries business. Cold storage is a way of storing fish at a certain temperature which allows fresh fish to be stored for long periods, even months, to prevent bacterial growth. This research aims to evaluate the implementation of the Standard Operating Procedure (SOP) for storing fish in cold storage using the First In First Out (FIFO) system and to evaluate the quality of the cooling system using temperature and humidity monitoring at Jaya Bahari cold storage. The method used in this research is measurement, interviews and literature study. The process stages in receiving fish products start from unloading fish, thawing frozen fish, weighing and testing samples, sorting and calculating the percentage of rejects, as well as temporary storage by looking at various obstacles during the process of receiving raw materials. The performance of the data logger and big data each showed results that were not much different with the respective tool accuracy values of 99.26% for temperature measurements and 99.83% for humidity measurements. Defrosting ice for 2 hours can save power by 4.37%.